Uit het leven - in de kunst. (Antwerpen : Museum van Hedendaagse Kunst, 1989)
d' Armagnac, Ben ; Armleder, John M. ; Artschwager, Richard ; Bijl, Guillaume ; Blaise, Dominique ; Brecht, George ; Callens, Mario ; Calzolari, Pier Paolo ; Carlier, Jan ; Christo ; Cole, Willem ; Copers, Leo ; Cragg, Tony ; François, Michel ; Huber, Stephan ; Jetelova, Magdalena ; Kiecol, Hubert ; Kosuth, Joseph ; Kounellis, Jannis ; Leccia, Ange ; Navez, Jean-Marc ; Nauma, Bruce ; Patella, Luca Maria ; Rombouts - Droste ; Ruthenbeck, Reiner ; Spoerri, Daniel ; Uecker, Gunther ; Ulrichs, Timm ; Vieille, Jacques ; Virnich, Thomas ; Woodrow
Uit het leven - in de kunst, Museum van Hedendaagse Kunst, Antwerpen, 16/12/89 - 21/01/90
boek